1995
DOI: 10.1161/01.hyp.26.6.1100
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Dysfunction in Short-term Experimental Diabetes

Abstract: Previous data showed that diabetes induced by streptozotocin for 5 days causes changes in arterial pressure control and baroreflex regulation of heart rate in male Wistar rats. The impairment of baroreflex may be related to autonomic neuropathy as described by several investigators. The aim of this study was to identify autonomic changes in short-term experimental diabetes in rats (induced for 5 days with streptozotocin 65 mg IP). Intra-arterial blood pressure signals were obtained from 6 control group and 7 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
103
3
22

Year Published

1997
1997
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(150 citation statements)
references
References 20 publications
22
103
3
22
Order By: Relevance
“…Studies from our laboratory have shown reduction in vagal tonus and maintenance of sympathetic tonus to the heart evaluated by pharmacological blockade with propranolol and methylatropine, respectively (14,16) (Figure 1), as previously demonstrated by Wegner et al (17), suggesting the presence of cardiac vagal neuropathy. Resting bradycardia in STZ-diabetic rats has been attributed to changes in the sinoatrial node with a consequent reduction in intrinsic HR (14,16,18), although functional alterations in the cholinergic mechanism cannot be excluded as a causal factor.…”
Section: Autonomic Control Of Heart Rate In Experimental Diabetessupporting
confidence: 79%
See 4 more Smart Citations
“…Studies from our laboratory have shown reduction in vagal tonus and maintenance of sympathetic tonus to the heart evaluated by pharmacological blockade with propranolol and methylatropine, respectively (14,16) (Figure 1), as previously demonstrated by Wegner et al (17), suggesting the presence of cardiac vagal neuropathy. Resting bradycardia in STZ-diabetic rats has been attributed to changes in the sinoatrial node with a consequent reduction in intrinsic HR (14,16,18), although functional alterations in the cholinergic mechanism cannot be excluded as a causal factor.…”
Section: Autonomic Control Of Heart Rate In Experimental Diabetessupporting
confidence: 79%
“…These data indicate that vagal function and intrinsic HR are decreased in short-and long-term STZ-induced diabetes in rats. The bradycardic response to methacholine injection was similar in control and diabetic rats 5 days after STZ administration (14). However, in 15-day STZ-treated rats this response was higher than in normal rats (10), suggesting that the early impairment in vagal tonus may be leading to an adaptive change in muscarinic receptors.…”
Section: Autonomic Control Of Heart Rate In Experimental Diabetesmentioning
confidence: 82%
See 3 more Smart Citations